Investigation on Double Oxide Film Initiated Pore Formation in Aluminum Casting Alloys - Gyarmati, Gábor; Fegyverneki, György; Tokár, Mónika; Mende, Tamás (International Journal of Engineering and Management Sciences, 2020)
The most common, and in fact, the most deleterious defects of aluminum casting alloys are the so-called double oxide films or bifilms, which have a central role in porosity formation, as they can easily unfurl and inflate into pores during the solidification of the alloys. Sr addition is generally used in the foundry industry for the modification of the eutectic Si phase of hypoeutectic Al-Si alloys. However, Sr microalloying usually leads to an increased pore formation tendency. As bifilms are preferred sites for pore formation, it should be expected that Sr additions have a significant effect on the number and/or the structure of double oxide films present in the melt. In this work, the relationship between Sr-concentration and the susceptibility to pore formation has been investigated through the evaluation of melt quality of melts which had different levels of Sr. The bifilm content of the melts was investigated by the analysis of K-mold specimens and X-ray computed tomography (CT) of reduced pressure test (RPT) samples. It was found that liquid alloys with a higher Sr concentration had a significantly greater tendency to pore formation, which can be explained by the presence of a larger number of bifilm defects in the liquid alloy.